Internet : La fin de la géographie ? - Frédéric Lasserre (Cybergeo, 2000)
The advent of the « new economy », embodied by the expansion of the internet, would be the signal of the end of geography and space. Distances are reportedly abolished as markets are from now on at a klick away. E-trade and the advent of Enterprise Ressource Planning (ERP) systems would provide firms with the tools they can use to free themselves of space. In fact, the internet and ERP are certainly changing the relationship between firms and their space and markets, but they do not disrupt them: location choices are still geographic. The need to transport faster and efficiently, brought about by the expansion of E-trade, establishes transportation as the effort of mastering space. It translates into the fast expansion of cargo airliners in logistics.